A Brief Review on the Pathological Role of Decreased Blood Flow Affected in Retinitis Pigmentosa - Yi Jing Yang; Jun Peng; Deng Ying; Qing Hua Peng (Journal of Ophthalmology)
Retinitis pigmentosa (RP) represents a clinically and genetically heterogeneous disease characterized by progressive photoreceptor loss. In recent years, research has been rarely made in blood flow affected in RP. The specific mechanism of blood flow affected in RP is not completely clear. A number of studies indicated that the decreased blood flow was related to RP. According to clinical observation and treatment experience, Chinese medicine considered that blood stasis runs throughout the RP disease progression, and the blood stasis corresponding to Chinese herbal medicine has a positive effect on the clinical treatment of RP. Therefore, we proposed that the decreased blood flow may participate in the lesion. In this article, we will review the findings on the decreased blood flow affected in RP from the perspective of modern medicine and Chinese medicine.